2009
DOI: 10.3174/ajnr.a1723
|View full text |Cite
|
Sign up to set email alerts
|

CT Angiography Source Images Predict Final Infarct Extent in Patients with Basilar Artery Occlusion

Abstract: BACKGROUND AND PURPOSE:The posterior circulation Acute Stroke Prognosis Early CT Score (pc-ASPECTS) is a 10-point grading system to quantify ischemic changes in the posterior circulation. We analyzed whether pc-ASPECTS on CT angiography (CTA) source images (CTASI) predicted the final infarct extent and hemorrhagic transformation (HT) rate in patients with basilar artery occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 25 publications
1
35
0
4
Order By: Relevance
“…need for the best outcome predicting neuroimaging model to obtain the optimal therapy. Concordant to other, smaller studies, the infarct detection rate of multimodal CT including CTP was significantly higher in all regions of the PC according to pc-ASPECTS (cerebellum, posterior cerebral artery territory, thalamus, brain stem/midbrain) and, therefore, provides the best outcome prediction [6,10] .…”
Section: Discussionsupporting
confidence: 64%
“…need for the best outcome predicting neuroimaging model to obtain the optimal therapy. Concordant to other, smaller studies, the infarct detection rate of multimodal CT including CTP was significantly higher in all regions of the PC according to pc-ASPECTS (cerebellum, posterior cerebral artery territory, thalamus, brain stem/midbrain) and, therefore, provides the best outcome prediction [6,10] .…”
Section: Discussionsupporting
confidence: 64%
“…18 However, the feasibility of MRI acquisition is limited in these frequently unstable patients. 19,20 We have recently demonstrated that CTA-SIs increase the sensitivity for early ischemic changes in the posterior circulation compared with noncontrast CT. 12,16 Compared with CTA-SI, perfusion CT techniques may provide additional diagnostic and prognostic information in patients with acute posterior circulation stroke. 21,22 The comparison of CTA, perfusion CT, and multimodal MRI to predict functional outcome and treatment response in patients with BAO could be the subject of future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Images were analyzed in a 3-readers consensus setting by stroke neurologists experienced in the interpretation of CTA-SI in acute ischemic stroke (A.M.D., I.D., V.P.). 12,16 Readers were blinded to clinical information. We graded hypoattenuating areas in posterior circulation territories with the pc-ASPECTS score and the Ponsmidbrain-index as described before (Figure 1).…”
Section: Image Analysismentioning
confidence: 99%
“…Doing nothing usually leads to death, but intervention, even if successful, can leave the patient in a vegetative state, especially when the lesions are widespread. The ASPECT scoring system in the posterior fossa lesion published by the Calgary team 25 suggests that with an ASPECT score Ď˝8, no good clinical outcome can be ex- …”
Section: Imaging-based Patient Selectionmentioning
confidence: 99%